2020
DOI: 10.29309/tpmj/2020.27.11.4821
|View full text |Cite
|
Sign up to set email alerts
|

Chronic indwelling foley catheter, a risk factor for catheter associated urinary tract infection.

Abstract: Catheter associated infection is one of commonest infection which affects hospital admitted patients. Indwelling urethral catheters which are kept in place for 30 days or less are called short term. Whereas, when catheter placement exceeds 30 days, it is known as chronic or long term. Objectives: This study was intended to investigate the frequency of urinary tract infection caused by chronic indwelling urethral catheters. Study Design: Cross Sectional study. Setting: Department of Urology & Renal Transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Instead, it is usually based on the clinician's experience, patients' conditions, surgical type, and perioperative factors. However, postoperative indwelling urethral catheterization can cause urinary tract infection to a certain extent, affecting the recovery of patients [8]. Previous studies have shown that the incidence of postoperative urinary retention is 5-70%, and the related risk factors have been identified in several surgical subspecialties [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is usually based on the clinician's experience, patients' conditions, surgical type, and perioperative factors. However, postoperative indwelling urethral catheterization can cause urinary tract infection to a certain extent, affecting the recovery of patients [8]. Previous studies have shown that the incidence of postoperative urinary retention is 5-70%, and the related risk factors have been identified in several surgical subspecialties [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the occurrence of CAUTI seriously affects hospital's reputation, reputation, brand, and sustainable development. Occupational exposure increases the risk of infection among medical staff [ 7 , 8 ]. Therefore, the study of CAUTI risk factors for critically ill patients is of great significance.…”
Section: Introductionmentioning
confidence: 99%